MEDICAL JOURNALISM IN PAKISTAN: WHERE DO WE STAND? - Sherin, Akhtar (Journal of Postgraduate Medical Institute, 2011)
In this era of advanced print and electronic media, internet and mass communication, the modern concept of Medical Journalism is not restricted to medical journals only and it involves the dissemination 1 th of health-related information through all mainstream media outlets . However since the late 18 and early th 19 centuray, the start of medical journals as specialized form of publications which was much different 2 from the communication media of that time was a real landmark in medical journalism . With ages, these 3 journals like medical schools and societies, had a great influence on medical profession and community . Medical journals are usually professional and scholorly oriented, with scientific and academic contribution from medical researchers. Unlike the ordinary newspapers, medical journals often target the readership of medical professionals instead of general public. In this editorial we will focus on various issues related to medical journals under the umbrella of medical journalism.